Inter-Role Conflict and Intention to Quit with Psychological Strain as a Mediator - Sundari, Sri; Tjahjono, Heru Kurnianto; Hartono, Arif; Prajogo, Wisnu (International Review of Management and Marketing, 2023)
Researches on inter-role conflict between work and family were initially carried out in developed countries with individualistic cultures based on western cultural contexts. However, currently, there has been an increasing number of researches on the same topic conducted in Asian countries with its collectivistic cultural contexts. One of the direct consequences of Work-family conflict is the emergence of psychological strain, thus leading to the intention to quit. This study examines the effect of work-family conflict and family-work conflict on the intention to quit working with the mediating role of psychological strain. The research was conducted on 270 employees of Rural Bank in Indonesia, a country with collectivistic culture. Data were analyzed using the Structural Equation Modeling method. Work-family conflict has a direct effect on intention to quit, as well as an indirect effect mediated by psychological strain. Psychological strain has a direct effect on intention to quit. Family-Work conflict had an indirect effect on intention to quit, mediated entirely by psychological strain. Psychological strain has mediated the effect of Work-family conflict and Family-work conflict on Intention to quit.